EFFECTS OF SUNFLOWER SEEDS ON CHOLESTEROL AND LOW-DENSITY LIPOPROTEIN LEVELS IN PATIENTS WITH DYSLIPIDEMIA - B, CHEENAM; P, LEENA; K, VIKAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was conducted with a goal to analyze and assess the effect of sunflower seeds on the serum cholesterol and low-density lipoprotein (LDL) levels. Methods: A total of 60 patients comprising 34 males and 26 females were selected for the given study. The patients were divided into case and control groups. Various anthropometric measurements such as weight, height, and blood pressure along with certain biochemical parameters including cholesterol and LDL were recorded for these patients pre- and post-supplementation of 2 g of sunflower seeds for 6 months. Results: The patients in the experimental group showed a significant and rapid difference (p<0.05) in comparison to the control intervention. The cholesterol levels in the case group reduced from 254.6±21.40 to 183.40±3.01 mg/dl, whereas, in control group, it reduced from 234.53±13.54 to 194.50±6.16 mg/dl. Similarly, the LDL levels in the case group decreased from 155.28±8.48 to 122.70±2.94 mg/dl; in contrast, in control group, it decreased from 159.53±6.04 to 140.53±1.11 mg/dl, respectively. Conclusion: The study conducted concluded that sunflower seeds can be used as an adjuvant in treating the raised cholesterol and LDL levels in the blood serum which could otherwise lead various cardiac disorders (both major and minor).